In vivo examination of the genotoxicity of the urban air and surface soil pollutant, 3, 6‐dinitrobenzo[e]pyrene, with intraperitoneal and intratracheal administration. Issue 10 (24th August 2011) - Kato, Tatsuya; Totsuka, Yukari; Hasei, Tomohiro; Watanabe, Tetsushi; Wakabayashi, Keiji; Kinae, Naohide; Masuda, Shuichi
<x xml:space="preserve">Abstract</x> 3, 6‐Dinitrobenzo[e]pyrene (3, 6‐DNBeP) was identified as a new potent mutagen toward Salmonella strains in surface soil and airborne particles. Because data of in vivo examination of the genotoxicity of 3, 6‐DNBeP are limited, micronucleus test was performed in peripheral blood and bone marrow, and comet assay in the lungs of mice treated with 3, 6‐DNBeP. In male ICR mice intraperitoneally (i.p.) injected with 3, 6‐DNBeP, the frequency of micronuclated polychromatic erythrocytes (MNPCEs) was increased in the peripheral blood and bone marrow after 24 h in a dose‐dependent manner. Compared to controls, the highest dose of 3, 6‐DNBeP (40 mg/kg B.W.) induced 7.3‐ and 8.7‐fold increases of MNPCE frequency in the peripheral blood and bone marrow, respectively. Furthermore, when 3, 6‐DNBeP was intratracheally (i.t.) instilled to male ICR mice, 3, 6‐DNBeP at the highest dose of 0.1 mg/kg body exhibited 3.1‐fold increase of DNA tail moment in the lungs at 3 h after the instillation compared to controls. The values of DNA tail moment at 9 and 24 h after the instillation were increased up to 3.5 and 4.2‐fold, respectively. These data indicate that 3, 6‐DNBeP is genotoxic to mammalians in in vivo and suggest that 3, 6‐DNBeP may be a carcinogenic compound present in the human environment. © 2011 Wiley Periodicals, Inc. Environ Toxicol 28: 588–594, 2013.